2000
DOI: 10.1104/pp.122.3.853
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of XET-Related Genes of Rice

Abstract: To elucidate the mechanism of internodal elongation in rice (Oryza sativa L.), we analyzed genes encoding xyloglucan endotransglycosylase (XET), a cell wall-loosening enzyme essential for cell elongation. Four rice XET-related (XTR) genes, OsXTR1, OsXTR2, OsXTR3, and OsXTR4, were isolated and their expression patterns in rice plants determined. The expression of the four XTR genes showed different patterns of organ specificity and responses to several plant hormones. OsXTR1 and OsXTR3 were up-regulated by gibb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 31 publications
8
85
0
1
Order By: Relevance
“…In accordance with its role in the construction and modification of cell wall architecture, XET activity and expression have been detected commonly in growing tissues (Fry et al, 1992;Pritchard et al, 1993;Palmer and Davies, 1996;Burstin, 2000;Uozu et al, 2000;Vissenberg et al, 2000Vissenberg et al, , 2001. In addition, XET also is clearly present in tissues in which expansion has ceased (Arrowsmith and de Silva, 1995;Xu et al, 1995;Palmer and Davies, 1996;Shimizu et al, 1997;Akamatsu et al, 1999;Burstin, 2000;Catalá et al, 2001;O'Donoghue et al, 2001).…”
Section: Introductionmentioning
confidence: 89%
“…In accordance with its role in the construction and modification of cell wall architecture, XET activity and expression have been detected commonly in growing tissues (Fry et al, 1992;Pritchard et al, 1993;Palmer and Davies, 1996;Burstin, 2000;Uozu et al, 2000;Vissenberg et al, 2000Vissenberg et al, , 2001. In addition, XET also is clearly present in tissues in which expansion has ceased (Arrowsmith and de Silva, 1995;Xu et al, 1995;Palmer and Davies, 1996;Shimizu et al, 1997;Akamatsu et al, 1999;Burstin, 2000;Catalá et al, 2001;O'Donoghue et al, 2001).…”
Section: Introductionmentioning
confidence: 89%
“…A wealth of evidence has been documented that high XTH enzyme activity and its mRNA level were closely correlated with the elongation zone of stems and roots and in ripening fruits in various plant species [23,26,27,[33][34][35][36][37][38]. Analysis of tobacco plants transformed with an antisense construction of NtXET-1 suggested that the reduction in Nt-XET-1 expression might be coupled with strengthening of cell walls [28].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 Primer sequences used in the RT-PCR analysis Gene name Accession Number Primer sequence [23,24], potato (xth1) (Genbank Accession No. CAJ77496), Arabidopsis (At-XTH15 and At-XTH22) [25], rice (OsXET_C) [26,27] and tobacco (NtXET_C) [28]. Amino-acid residues that are conserved in at least seven of the ten sequences are shaded, whereas amino-acids that are identical in all ten proteins are shown in black.…”
Section: Isolation and Identification Of The Full-length Caxthmentioning
confidence: 99%
See 1 more Smart Citation
“…However, H4, H3 (two molecular markers for the S phase [36]), and EXPB6 (a member of the β-expansin gene family critical for cell elongation in deep water rice [37]) expressions were not obviously altered in the lc2-1 mutant ( Figure 6A, bottom panel). Analysis of the expression of cell-elongation-related genes including XTR1 (encoding xyloglucan endotransglycosylase, the cell-wall loosening enzyme necessary for cell elongation [38]) showed that XTR1 expression was enhanced in the mutant ( Figure 6A, upper panel). Collectively, the results of our study suggest that LC2 mainly regulates cell division through suppressing the expression of cell-division-related genes.…”
Section: Lc2 Is Expressed In Aerial Parts and Induced By Hormonesmentioning
confidence: 99%